New Labour's women MPs : women representing women - Childs, Sarah, 1969- (Routledge, 2004)
Drawing on interviews with over half of new Labour women MPs, Sarah Childs reveals how the women experienced being MPs, and explores whether they acted for and like women - in constituencies, in Parliament and in government.